2011
DOI: 10.1016/j.jneuroim.2010.10.037
|View full text |Cite
|
Sign up to set email alerts
|

A case for regulatory B cells in controlling the severity of autoimmune-mediated inflammation in experimental autoimmune encephalomyelitis and multiple sclerosis

Abstract: Multiple sclerosis (MS) is considered to be a T cell-mediated autoimmune disease that results in the presence of inflammatory lesions/plaques associated with mononuclear cell infiltrates, demyelination and axonal damage within the central nervous system (CNS). To date, FDA approved therapies in MS are thought to largely function by modulation of the immune response. Since autoimmune responses require many arms of the immune system, the direct cellular mechanisms of action of MS therapeutics are not definitivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 130 publications
2
46
0
4
Order By: Relevance
“…Importantly, in the absence of IL-10-producing B cells, mice are not able to recover from EAE. 60,64 In a recent study, fusokine GIFT15-induced Breg cells are shown to secrete IL-10 and express MHC I, MHC II, and surface IgM and IgD. Moreover, mice with EAE undergo complete remission after the intravenous transfer of GIFT15-Breg cells.…”
mentioning
confidence: 99%
“…Importantly, in the absence of IL-10-producing B cells, mice are not able to recover from EAE. 60,64 In a recent study, fusokine GIFT15-induced Breg cells are shown to secrete IL-10 and express MHC I, MHC II, and surface IgM and IgD. Moreover, mice with EAE undergo complete remission after the intravenous transfer of GIFT15-Breg cells.…”
mentioning
confidence: 99%
“…8,11,12 Rezultati ovog istraživanja su pokazali i da je intratekalna produkcija antitela relevantna za patofiziološke procese u razvoju MS, ali i da se obrasci oligoklonskih traka razlikuju među pacijentima. Taj podatak ukazuje da se kod obolelih razvija specifičan odgovor B limfocita ali jedinstven za svakog pacijenta.…”
Section: Funkcija B Limfocita Značajunclassified
“…Taj podatak ukazuje da se kod obolelih razvija specifičan odgovor B limfocita ali jedinstven za svakog pacijenta. 11,12 Oligoklonske trake nisu specifične za MS. Njihovo prisustvo se takođe može ustanoviti i kod infektivnih oboljenja CNS, kao što su neuroborelioza, herpes simplex enchephalitis, HIV infekcija ili subakutni sklerozirajući panencefalitis, pri čemu prisutna antitela specifično prepoznaju antigene koji učestvuju u nastanku bolesti. 8 Iako su intratekalna antitela predmet brojnih istraživanja već više decenija, njihov značaj u patogenezi, kao i njihova specifičnost, odnosno ciljni autoantigeni, još uvek nisu precizno definisani.…”
Section: Funkcija B Limfocita Značajunclassified
See 1 more Smart Citation
“…They also function as antigen-presenting cells, contribute to T-cell activation and produce effector cytokines that are considered modulators of the local immune environment. Recent evidence in MS also suggests a role in formation and maintenance of new lymphoid foci within the CNS [3].…”
Section: Introductionmentioning
confidence: 99%